Young onset mitochondrial encephalomyopathy, lactic acidosis and stroke-like episodes (MELAS) syndrome: a case report. - Kartik Goel; Divyanshu Singh; Ravi Bhargav; Harsh Kansagara; Shailesh Kumar; Rupesh Yadav (Critical Care Innovations)
Mitochondrial Encephalomyopathy, Lactic Acidosis, and Stroke-like Episodes Syndrome (MELAS) is a rare mitochondrial disorder characterised by diverse neurological and systemic manifestations. The key underlying mechanism of the disease is related to protein synthesis, energy depletion, and nitric oxide defciency. We present a case from a tertiary care hospital of a 19-year-old male with a history of seizure disorder and progressive neurological deficits. The patient was evaluated using clinical evaluations, laboratory tests, and radiological imaging to rule out the most serious complications. His symptoms included bilateral sensorineural hearing loss, visual disturbances, and recurrent headaches associated with vomiting. Neurological examination revealed signs of bilateral sensorineural hearing loss, visual field deficits, and asymmetric weakness in the four limbs. Diagnostic workup, including MRI findings of parieto-occipital lesions and elevated lactate levels, supported the diagnosis of MELAS syndrome. Genetic testing confirmed the presence of the m.3243A>G mutation in mitochondrial DNA. After a 2-week hospital stay, the patient was discharged with a follow-up plan. The main goals of treatment are to effectively manage disease complications and to enhance the patient's overall quality of life. Management involved the adjustment of antiepileptic therapy and initiation of mitochondrial supplements. This case underscores the clinical spectrum and diagnostic challenges of MELAS syndrome, emphasising the importance of early recognition and tailored treatment strategies to optimise patient outcomes.